Крутая дамочка, или Нежнее чем польская панна: [роман] / Екатерина Вильмонт - Вильмонт Екатерина Николаевна (АСТ, 2008)
Экземпляры: ф. 9 (20150205) / Инвентарный номер: 49649 / Цена: / Авт.знак: В 46 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44